Assessment of Drug Therapy Problems Among Type 2 Diabetes Patients with Hypertension Comorbidity in Indonesia - Julaeha Julaeha; Ery Fudjiati; Aprilita Rina Yanti Eff (Borneo Journal of Pharmacy, 2020)
Type 2 diabetes mellitus (T2DM) is a major chronic disease that affects a large number of people worldwide. Hypertension is a common disease comorbidity among T2DM patients, and often those patients received polypharmacy and complex treatment in long term duration. This condition may lead to an increased risk of drug therapy problems (DTPs). This study aimed to assess and determine potential drug therapy problems in type 2 diabetic patients with hypertension comorbidity. Retrospective cross-sectional design was conducted in a hospital setting, especially data sources from the prescription of ambulatory T2DM patients with hypertension. A total of 190 patients were studied. More than half of the participants were female (53.68%). The majority age range of participants was 50-59 years (46.84%). Almost all antidiabetic agents were prescribed as polypharmacy (73.16%). Metformin was the most antidiabetic agent prescribed as monotherapy and combination therapy (63.16%). Almost all antihypertensive agents were prescribed as polypharmacy (63.26%). Amlodipine was the most antihypertensive agent prescribed as monotherapy and combination therapy (34.74%). Among the study participants, 56.84% have at least one of DTPs. Adverse drug reaction was the most frequent (47.22%), followed by ineffective drug therapy (29.63%). Since the potential of DTPs in T2DM patients with hypertension comorbidity is relatively high, early identifying, resolving, and preventing drug therapy problems by the pharmacist is needed to achieve goals of treatment.